Perspectives on premetamorphic stratabound tourmalinites - Slack,J.F. (Journal of Geosciences, 2022)
Stratabound tourmalinites are metallogenically important rocks that locally show a close spatial association with diverse types of mineralization, especially volcanogenic massive sulfides (VMS) and clastic-dominated (CD) Zn-Pb deposits. These tourmalinite occurrences pan the geologic record from Eoarchean to Jurassic. Host lithologies are dominated by clastic metasedimentary rocks but in some areas include metavolcanic rocks, marble, or metaevaporites. Stratabound and stratiform (conformable) tourmalinites commonly display sedimentary structures such as graded beds, cross-beds, and rip-up clasts. In most cases, field and microtextural relationships are consistent with a synsedimentary to the early diagenetic introduction of boron as a precursor to tourmaline formation. Whole-rock geochemical data for major, trace, and rare earth elements (REE) provide valuable insights into tourmalinite origins. Al-normalized values relative to those for least-altered host metasedimentary rocks suggest that tourmalinites in proximal settings at or near hydrothermal vent sites characterized by high fluid/rock regimes (e.g., Sullivan Pb-Zn-Ag deposit, Canada) have very different signatures than those in low fluid/rock, distal settings (e.g., Broken Hill Pb-Zn-Ag deposit, Australia). The high fluid/rock regimes at Sullivan show large mass changes of +60 % for Mg and +180 % for Mn, as well as large variations in abundances of light and middle REE. In contrast, tourmalinite formation in low fluid/rock regimes yields minimal Al-normalized changes in major elements, trace elements, and REE. Boron isotope values of tourmalinite-hosted tourmaline vary widely from -26.1 to +27.5 ‰, and are attributed mainly to boron sources (e.g., sediments, evaporites) with generally minor influence from processes such as formational temperature, fluid/rock ratio, and secular variation in seawater δ11B values.Laterally extensive stratiform tourmalinites formed mainly by syngenetic or early diagenetic processes on or beneath the seafloor. The syngenetic process is attributed to the interaction of vented B-rich brines with aluminous minerals in sediments, whereas the diagenetic process involves the selective replacement of aluminous sediments by B-rich fluids. Modern examples of tourmalinites, as yet undiscovered, may exist in metalliferous sediments of the Red Sea and the eastern Pacific Ocean, in altered volcaniclastic sediments within active seafloor-hydrothermal systems of the South Pacific, and in hydrothermal mounds and vents associated with mafic sill complexes in extensional basins as in the North Sea and South China Sea. Stratabound tourmalinites that contain base-metal sulfides, high Mn concentrations (>1 wt. % MnO), or positive Eu anomalies can be valuable exploration guides for base-metal sulfide deposits in sedimentary and volcanic terranes.
Keywords: Tourmalinite; Metallogeny; Syngenetic; Diagenetic; Boron Isotopes; Genetic Models